Crack propagation behaviors in a nanoparticle‐filled rubber studied by in situ tensile electron microscopy. Issue 7 (31st May 2021) - Watanabe, Daisuke; Miyata, Tomohiro; Nagao, Tomohiko; Kumagai, Akemi; Jinnai, Hiroshi
Abstract: Although fracture resistance is critical for rubber materials, the fracture mechanisms are poorly understood from a microscopic perspective. In this study, a crack propagation process in rubber with silica nanoparticles, which is commonly used to enhance the mechanical properties of rubber materials, was successfully observed in situ with nanoscale resolution using transmission electron microscopy (TEM). The consecutive time‐sliced TEM images clarified that the crack tip propagated along the interfaces between the rubber matrix and aggregates of silica nanoparticles (rubber‐aggregate interfaces). Moreover, the path and propagation rate of the crack were significantly affected by the heterogeneous distribution of the silica aggregates, which resulted in a "stick–slip" propagation behavior of the crack tip. Detailed spatial strain analysis revealed that the local maximum principal strain ( ε max ) around the crack tip was nonuniform. The crack tip propagated through regions with large ε max, delaminating the rubber‐aggregate interfaces. This study successfully demonstrated that the heterogeneous distribution of nanoparticles significantly affects the fracture behavior of nanoparticle‐filled rubbers. Abstract :